2003
DOI: 10.1074/jbc.m301147200
|View full text |Cite
|
Sign up to set email alerts
|

LIS1 Missense Mutations

Abstract: Mutations in one allele of the human LIS1 gene cause a severe brain malformation, lissencephaly. Although most LIS1 mutations involve deletions, several point mutations with a single amino acid alteration were described. Patients carrying these mutations reveal variable phenotypic manifestations. We have analyzed the functional importance of these point mutations by examining protein stability, folding, intracellular localization, and protein-protein interactions. Our data suggest that the mutated proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 47 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…S1 A; unpublished data). A similar distribution was seen by Caspi et al (2003) in cells expressing GFP-α1. Catalytically inactive α1 S47A and α2 S48A, as well as α1 E38D and α2 E39D, were similarly localized (Fig.…”
Section: Resultssupporting
confidence: 74%
“…S1 A; unpublished data). A similar distribution was seen by Caspi et al (2003) in cells expressing GFP-α1. Catalytically inactive α1 S47A and α2 S48A, as well as α1 E38D and α2 E39D, were similarly localized (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Intragenic LIS1 or DCX mutations in patients with lissencephaly include missense amino acid changes and truncations ( Cardoso et al, 2000 , 2002 ; Gleeson et al, 2000 ). The mutant proteins are either incorrectly folded ( Sapir et al, 1999 ; Caspi et al, 2003 ) and fail to associate with binding partners ( Feng et al, 2000 ) or fail to bind MTs ( Taylor et al, 2000 ), but no data exist on the effect of these mutations on migration. To assess the function of the mutant proteins quantitatively, patient-related mutant Dcx (R89G, T203R, 303stop; Gleeson et al, 1998 ) or Lis1 (H149R, S169R, D317H; Lo Nigro et al, 1997 ; Pilz et al, 1999 ) was overexpressed.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first demonstration of a system that can be used to test the effect of patient mutations on neuronal migration. Previous reports have demonstrated that Lis1 with introduced patient mutations is either unstable ( Sapir et al, 1999 ), displays abnormal folding ( Caspi et al, 2003 ), or cannot properly bind to ligands such as mNudE ( Feng et al, 2000 ). Dcx with introduced patient mutations leads to impaired MT polymerizing ability ( Sapir et al, 2000 ; Taylor et al, 2000 ) or cannot bind to the FIGQY-phosphotyrosine motif in neurofascin ( Kizhatil et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…A central molecular mechanism for microcephaly in MCPH2 may be a deficiency or dysfunction of WDR62 at the spindle pole of dividing cells due to processes such as non-expression, loss of essential spindle targeting domains, misfolding or rapid degradation of the mutant protein [39]. For WDR62 it has been recently demonstrated that siRNA downregulation in murine neural progenitors through in utero electroporation induces early cell cycle exit and a reduced proliferative capacity.…”
Section: Discussionmentioning
confidence: 99%